Heterogeneous impacts of sentencing decisions - Andrew Jordan; Ezra Karger; Derek A. Neal (Federal Reserve Bank of Chicago, 2022)
We examine 70,581 felony court cases filed in Chicago, IL during the period 1990-2007. We exploit case randomization to assess the impact of judge assignment and sentencing decisions on the arrival rates of new charges. Relative to prior research, we document an important source of heterogeneity in the impact of incarceration on recidivism. Incarceration creates lasting reductions in recidivism among first offenders but not repeat offenders. We present suggestive evidence that these reductions among first offenders primarily reflect outcomes for offenders who live in lower-crime areas of the city and are not involved in the drug trade. During our sample period, Illinois parole officers were able to issue arrest warrants for former inmates under their supervision. These powers place former inmates at significant risk of returning to prison as punishment for violations of technical conditions of their supervision. However, we find no evidence that these police powers increased the arrival rate of new charges against formerly incarcerated offenders. Incarceration does not reduce the arrival of new criminal charges among repeat offenders, and this outcome is not the result of parole officers over-policing repeat offenders.
Keywords: 330; recidivism; sentencing decisions; heterogeneity; Legal Procedure; the Legal System; and Illegal Behavior: General; Criminal Law